Blue and red luminescence from Si ion-irradiated SiO2/Si/SiO2 layers - Son, JH; Kim, TG; Shin, SW; Kim, HB; Lee, WS; Im, S; Song, JH; Whang, CN; Chae, KH (ELSEVIER, 2001)
Photoluminescence (PL) from the Si ion-irradiated SiO2/Si/SiO2 layers on Si substrate at room temperature has been studied to elucidate the origins of the blue and red luminescence. A luminescence band around 450 nm was observed from as-irradiated sample, which was found to be originated from the diamagnetic defect known as Bz band generated by Si ion irradiation. The intensity of this band increases with the increase of annealing temperatures up to a critical temperature. After annealing at 1100 degreesC, the defect-related PL peaks around 450 and 600 nm disappear and a new PL peak appears around 700 nm. This luminescence band is attributed to similar to5 nm-sized Si nanocrystals formed along the Si layer between SiO2 layers. (C) 2001 Elsevier Science B.V. All rights reserved.